Activation of phagocytic cells by Staphylococcus epidermidis biofilms: effects of extracellular matrix proteins and the bacterial stress protein GroEL on netosis and MRP-14 release - Dapunt, Ulrike A.; Gaida, Matthias; Meyle, Eva; Prior, Birgit; Hänsch, Gertrud Maria (Pathogens and disease, 2016)
We were able to identify the bacterial heat shock protein GroEL as a neutrophil-activating entity within the biofilm matrix and for the first time demonstrate i